1999
DOI: 10.1037/0735-7044.113.6.1204
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal 192 IgG-saporin lesions of basal forebrain cholinergic neurons selectively impair response to spatial novelty in adult rats.

Abstract: The role of the developing cholinergic basal forebrain system on cognitive behaviors was examined in 7 day-old rats by giving lesions with intraventricular injections of 192 IgG-saporin or saline. Rats were subjected to passive avoidance on postnatal days (PND) 22-23, water maze testing on PND 50-60, and a open-field test (in which reactions to spatial and object novelty were measured) on PND 54. Behavioral effects of the lesions were evident only in the open-field test with 5 objects. Unlike controls, the les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 56 publications
(87 reference statements)
1
30
1
Order By: Relevance
“…Previous work in mice and rats, using paradigms similar to the OFOR task used by us, show that normal rodents habituate to objects, as indicated by a gradual decrease in exploration between S2 and S4; but they increase their exploration in response to spatial object displacement and object novelty (Poucet, 1989;Thinus-Blanc et al, 1996;Ricceri et al, 1999;Frick and Gresack, 2003). To what extent animals increase their exploration of all objects or only that of the displaced objects, relative to the unchanged objects, appears to depend on sex and strain variables (Poucet, 1989;Thinus-Blanc et al, 1996;Frick and Gresack, 2003).…”
Section: Behavioral Effectsmentioning
confidence: 61%
See 2 more Smart Citations
“…Previous work in mice and rats, using paradigms similar to the OFOR task used by us, show that normal rodents habituate to objects, as indicated by a gradual decrease in exploration between S2 and S4; but they increase their exploration in response to spatial object displacement and object novelty (Poucet, 1989;Thinus-Blanc et al, 1996;Ricceri et al, 1999;Frick and Gresack, 2003). To what extent animals increase their exploration of all objects or only that of the displaced objects, relative to the unchanged objects, appears to depend on sex and strain variables (Poucet, 1989;Thinus-Blanc et al, 1996;Frick and Gresack, 2003).…”
Section: Behavioral Effectsmentioning
confidence: 61%
“…Lack of response to spatial change is generally associated with damage to, or abnormalities in, brain centers involved in spatial learning and memory such as the hippocampus and neocortex (Poucet, 1989;Save et al, 1992;Thinus-Blanc et al, 1996;Hohmann et al, 1999;Ricceri et al, 2002). However, the response to object novelty is usually left intact in these paradigms (Save et al, 1992;Ricceri et al, 1999).…”
Section: Behavioral Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…task was adapted from a task developed by Ricceri et al [100] in accordance with parameters introduced by Poucet [95]. The OFOR task was performed in a round enclosure of approximately 3 feet in diameter, surrounded by walls of about ten inches high that lean outward at a slight angle of about 15 degrees (commercial plastic baby pool).…”
Section: Open Field Object Recognition (Ofor)-thismentioning
confidence: 99%
“…Moreover, change in object positions, after the mice had established a "routine" of exploring the same 5 objects in the same locations for three six minute sessions, resulted in a significant 30% decrease (p=0.024) of all exploratory activity in lesioned male mice. Changing object position is ordinarily used to assess spatial learning and memory and normal mice increase exploration, particularly of the displaced objects [95,100,103]. The results of the OFOR analysis showed that lesioned mice acquired and retained spatial information relatively normally, but had an abnormal response to this challenge that suggested aversion to spatial change.…”
Section: Open Field Object Recognition (Ofor)mentioning
confidence: 99%